Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Construction of covalent organic framework electrospun composite nanofiber membranes for the efficient extraction and detection of phenylurea herbicides - Xue-Ying Rui; Bao-Zhu Jia; Peng Wen; Hong Wang; Hong-Tao Lei; Lin Luo; Zhen-Lin Xu (Food Chemistry, 2025)

Synergistic lattice engineering and surface passivation via cerium modification for robust ultrahigh-nickel layered oxide cathodes - Lunhao Deng; Rui Zhou; Jie Chen; Xiaotian Xu; Yuanyuan Chen; Xinyu Zhao; Liang Luo; Wang Xiang; Xiangwan Lai; Yingjie Zhang; Xianshu Wang; Ding Wang; et al. (Chemical Engineering Journal, 2025)

UV-switchable dual-mode sensing in a lead-free CsCu2I3 perovskite sensor for selective detection of mixed amines - Rui Wu; Qingyi Guan; Mingji Xu; Ruixiang Li; Shu Chen; Chunhua Luo; Hui Peng; Hechun Lin (Chemical Engineering Journal, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Telaprevir attenuates caspase-11-dependent pyroptosis in mouse heart following ischemia/reperfusion via inhibition of MALT1/TRAF6 pathway - Ming-Rui Li; Bi-Feng Yao; Can Tang; Xiu-Ju Luo; Jun Peng (Toxicology and Applied Pharmacology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Multidimensional analysis of sensory perception and neurophysiological responses to marinated beef cooked by diverse methods - Tianyi Yang; Wei Jiang; Chencheng Luo; Jin Hu; Wei Xu; Peng Zhang; Xiaofei Jin; Yuxuan Zhou; Rui Liu; Zhiyu Qian; Yamin Yang (Innovative Food Science & Emerging Technologies, 2025)

A promising mutant strain of Pyropia haitanensis ZD-2 for floating cultivation with enhanced growth, holdfast strength, and desiccation tolerance - Yujie Wang; Qijun Luo; Juanjuan Chen; Rui Yang; Peng Zhang; Tiegan Wang; Haimin Chen (Journal of Applied Phycology, 2025)

Impact of the drying process on the flavor characteristics of two economically important laver species, Pyropia haitanensis and Neopyropia yezoensis - Yuting Zhang; Juanjuan Chen; Yongbo Huang; Qijun Luo; Rui Yang; Peng Zhang; Tiegan Wang; Haimin Chen (Food Chemistry, 2025)

Research progress of non-coding RNA regulating the role of PANoptosis in diabetes mellitus and its complications - Guangyu Han; Kaibo Hu; Tianfeng Luo; Wenting Wang; Deju Zhang; Liu Ouyang; Xiao Liu; Jianping Liu; Yuting Wu; Jianqi Liang; Jitao Ling; Yixuan Chen; et al. (Apoptosis, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Metabolome analysis reveals the involvement of oxylipins in regulating the maturation of conchosporangia in Pyropia haitanensis - Yi Liu; Haike Qian; Shanshan Zhu; Tingting Niu; Qijun Luo; Juanjuan Chen; Rui Yang; Peng Zhang; Tiegan Wang; Haimin Chen (Algal Research, 2025)

Corrigendum to “Antiviral effects of duck type I and type III interferons against Duck Tembusu virus in vitro and in vivo” [Vet. Microbiol. 287 (2023) 109889] - Peng Zhou; Dejian Liu; Qingxiang Zhang; Wanrong Wu; Dong Chen; Rui Luo (Veterinary Microbiology, 2025)

The extensive cultivation of Pyropia haitanensis along the coastal areas influences the ecological dynamics of nearby intertidal mudflat pond water - Peihao Liu; Qijun Luo; Shanshan Zhu; Juanjuan Chen; Rui Yang; Tingting Niu; Tiegan Wang; Peng Zhang; Haimin Chen (Frontiers in Marine Science, 2025)
Introduction The aquaculture in intertidal mudflat ponds on the coast of the East China Sea typically coexists with oceanic seaweed cultivation in the nearby open water area, forming an interconnected aquatic ecosystem. This study aimed to understand the impact of the seaweed cultivation on the water quality and microbial communities in their neighboring intertidal mudflat ponds. Methods A unique recirculating culture system was established, integrating seaweed farming in marine areas with aquaculture ponds on mudflats, and incorporating an effluent treatment process for added efficiency. Water samples were collected from three sites, including open water areas with or without seaweed ( Pyropia haitanensis ) cultivation, the aquaculture mudflat ponds, and effluent water ponds, with control sites for comparison. The dynamic diversity patterns and structure of microbial communities were determined by 16S and 18S rRNA sequencing, and the environmental factors were measured. Results In the offshore aquaculture area, the cultivation of P. haitanensis increased the dissolved oxygen and pH, decreased inorganic nutrients, reduced the alpha diversity of bacteria, established the dominance of Proteobacteria, but did not influence the composition of microeukaryotes. These changes in the seawater subsequently affected the dynamics in the corresponding aquaculture ponds, where the water quality was improved, the microbial diversity was enhanced, and the abundance of functional bacteria such as Microbacteriaceae was increased. According to the co-occurrence network analysis, the cultivation of P. haitanensis potentially improved the stability of the microbial communities in both the offshore aquaculture area and the onshore aquaculture ponds and allowed them to resist stress better. In addition, after the effluent from the aquaculture ponds was purified in the treatment ponds with mangroves and oysters, the water quality improved and the abundances of Dinophyceae and Bacillariophyta decreased. Discussion This study highlights the positive effects of P. haitanensis cultivation on water quality and microbial stability in adjacent aquaculture ponds.

Monoclonal antibody-based lateral flow immunoassay:An alternative solution for the rapid detection of formaldehyde - Lin Luo; Rui Liang; Zhan-Peng Chen; Bao-Zhu Jia; Ai-Fen Ou; Rong-Rong Zhan; Hong Wang; Hong-Tao Lei; Zhen-Lin Xu (Food Bioscience, 2025)

Water-triggered stimuli-responsive luminescent crown-ether-coordinated cuprous bromides for multi-functional applications - Rui Wu; Hao Yang; Meifeng Jiang; Hui Tong; Xinyu Hu; Ziyang Liu; Chunhua Luo; Hui Peng; Hechun Lin (Chemical Engineering Journal, 2025)